Associations of Exercise Tolerance With Hemodynamic Parameters for Pulmonary Arterial Hypertension and for Chronic Thromboembolic Pulmonary Hypertension. Issue 5 (September 2017) - Tsuboi, Yasunori; Tanaka, Hidekazu; Nishio, Ryo; Sawa, Takuma; Terashita, Daisuke; Nakayama, Kazuhiko; Satomi-Kobayashi, Seimi; Sakai, Yoshitada; Emoto, Noriaki; Hirata, Ken-ichi
Abstract : Purpose: Pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) are the main subgroups of pulmonary hypertension (PH). Despite differences in their etiologies, both diseases are characterized by vascular remodeling, resulting in progressive right heart failure. Noninvasive periodic evaluation of exercise tolerance has become increasingly important. Cardiopulmonary exercise testing (CPET) and a 6-minute walk test (6MWT) are now both recommended for evaluating exercise tolerance, but there is insufficient knowledge about possible differences in the associations of exercise tolerance with right heart catheterization (RHC) data for patients with PAH and CTEPH. Methods: A retrospective study was performed with 57 patients with PH (24 with PAH and 33 with CTEPH) all of whom underwent echocardiography, CPET, 6MWT, and RHC. Results: For both patients with PAH and CTEPH, peak heart rate during CPET was significantly higher than that from 6MWT, whereas minimum peripheral oxygen saturation during CPET and 6MWT was similar. For patients with PAH, significant correlations were observed between peak O2 and cardiac index (CI) ( r = 0.59; P = .002) and between E / CO2 slopes and CI ( r =−0.46, P = .02), as well as a nonsignificant correlation tendency for peak O2 and pulmonary vascular resistance (PVR) and for E / CO2 and PVR ( r =−0.39; P = .05; and r = 0.39; P = .06, respectively). For patients with CTEPH, however, a significant correlation was observed only between E / CO2 slopes and CI ( r =−0.38; P = .02). Conclusion: PH etiology should be considered when assessing exercise tolerance, whereas CPET can be effective in addition to hemodynamic assessment by means of RHC for periodic evaluation during followup. Abstract : We studied 57 patients with pulmonary hypertension (PH): 24 with pulmonary arterial hypertension (PAH) and 33 with chronic thromboembolic PH (CTEPH). Associations between exercise tolerance and hemodynamic parameters were different for patients with PAH and CTEPH despite similar disease characteristics. Therefore, PH etiology should be considered when assessing exercise tolerance.